Penentuan Prioritas Perbaikan pada Mesin Sizing untuk Meningkatkan Kualitas Draft Sizing dengan Menggunakan Metode Grey FMEA - Dora Virma Yolanda Gultom; Yunita Primasanti; Agung Widiyanto Fajar Sutrisno (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
Draft Sizing quality is a crucial issue in the sizing department. There were 14,881 total warp breaks woven during the November to December period. This led to low draft sizing quality. This research aims to improve the quality of draft sizing by applying Grey Theory in traditional FMEA. This type of research uses descriptive qualitative research. Data collection techniques using questionnaires, observations and interviews at PT Delta Merlin Dunia Tekstil V. The data processing method in this study uses Grey Theory and FMEA methods. The results of this study indicate that from the sizing process flow there are 7 sizing areas that are potential failures of draft sizing and show that out of 26 priority sequences there are 10 different priorities and 16 the same priority. Determination of improvement priorities is based on the value of the smallest degree of relationship, namely Potential causes PIV is not stable in the size box area with the result of the degree of relationship value of 0.356, Potential causes PIV is not stable in the head stock area with the result of the degree of relationship value of 0.382, Potential Causes Kampas wear in the creel beam stand area with the result of a degree value of 0.477, Potential Causes Gear and Chain wear in the dryer cylinder area with the result of a degree value of 0.453 and Potential Causes The break regulator hole is not symmetrical (pneumatic piston is not aligned) in the creal beam stand area with the result of a degree value of 0.466. This research can recommend the sizing improvement process based on proposed improvements or maintenance schedules on the sizing machine, using Grey Theory in the FMEA method to improve the quality of the sizing draft.